The Effect of Scramble Learning Model on Student Learning Outcomes - Yuliana, Yuyun; Nurhayati, Enung (IKIP Siliwangi, 2025)
The issue of inferior learning results resulting from the learning process's propensity to employ less creative learning models serves as the backdrop for this study. This study aims to identify the effect of the scrumble learning model on learning outcomes. This research method uses literature reviews from 3 databases, namely Google Scholar, Garuda Portal, and ERIC using the keywords